Stwierdzane niezgodności norm wyższego i niższego rzędu a pojęcia niezgodności norm - Wojciechowski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The main thesis of the paper claims that judgments of constitutional courts explicitly stating a conflict between lower order norm and norm of higher order are not an instance of formal conflict of norms. The reason for this lies in the nature of constitutional norms and the norm being subject of inquiry. Constitutional norms are mostly norms granting competence, while norms being subject of inquiry are rules of conduct. Therefore, reasoning of constitutional court includes evaluation of an act of legislator, rather than evaluation of an established norm. For instance, if there is a statute enacted stating a rule that vacation legis will consist of seven days and constitutional court, as a consequence of a principle of proper legislation, will state what such seven day rule is in conflict with that constitutional principle, then there is no formal conflict of those norms. It is an act of stating such a rule by the lawmaker that is a subject of inquiry. Unconstitutionality lies in b r e a c h i n g a constitutional norm by the lawmaker act, not in the formal conflict of two norms. In this sense constitutional court is not that far away from what common courts do. This observation helps to provide additional account for potential controversy of constitutional courts judgments.
Keywords: orzeczenia sądów konstytucyjnych; normy konstytucyjne; normy niższego rzędu; normy wyższego rzędu